2021
DOI: 10.1002/acm2.13371
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: On the impact of the kV imaging configuration on doses from planar images during motion‐synchronized treatments on Radixact®

Abstract: The Synchrony motion management system on the Radixact linear accelerator (Accuray Inc.) uses kilovoltage (kV) planar radiographs to localize the target during helical tomotherapy treatments. [1][2][3] The dose the patients receive from these kV radiographs has been investigated in several previous publications. 4,5 A description of the motion management system can also be found in these publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A study by Ferris showed that when the kV imaging system was upgraded from Gen1 to Gen2, the kV doses per mAs were found to be reduced by ~66% for planar images during motion-synchronized treatments on Radixact ® [ 17 ]. Hence, with the improved target tracking accuracy and the decrease in the kV imaging dose, the Gen2 kV system is a better option than the Gen1 system for Radixact ® Lung Synchrony ® treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ferris showed that when the kV imaging system was upgraded from Gen1 to Gen2, the kV doses per mAs were found to be reduced by ~66% for planar images during motion-synchronized treatments on Radixact ® [ 17 ]. Hence, with the improved target tracking accuracy and the decrease in the kV imaging dose, the Gen2 kV system is a better option than the Gen1 system for Radixact ® Lung Synchrony ® treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There are two versions of Radixact available for clinical use, with and without kV computed tomography (kVCT) acquisition capabilities. This hardware difference affects the kV source-to-axis distance (SAD) and source-to-detector distance, which are 57.5 cm and 113.5 cm, respectively, for the standard configuration and 104.8 cm and 156.2 cm for the extended (with kVCT capabilities) configuration [12]. Currently, the imaging protocols (mAs, kVp) available on each configuration are the same despite the difference in SAD (e.g., the 'Large Thorax' protocol is 120 kVp 1.6 mAs for both).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the imaging protocols (mAs, kVp) available on each configuration are the same despite the difference in SAD (e.g., the 'Large Thorax' protocol is 120 kVp 1.6 mAs for both). Recent work has indicated that dose per mAs to the patient from planar radiographs is about 66% less for the extended configuration, primarily due to the extended distance [12]. It is hypothesized that image quality and fiducial visibility will be different between the two versions (for the same kV and mAs) since output is very different.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations